The Effect of Work Load and Organizational Culture onHealth Workers Satisfaction at Dr. Soepraoen Hospitals Malang - R.A Rengganis Ularan; Fita Rusdian Ikawati; Anis Ansyori (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2021)
Job satisfaction is one of several factors that are very important to get maximum results. Satisfaction can be influenced by several factors, organizations need to pay attention to these factors to increase employee job satisfaction. The research objective was to determine the influence of workload and organizational culture on work satisfaction of health workers at Tk. II DR. Soepraoen Malang. The number of samples taken was 55 health workerswith the saturated sample method. Methods of datacollection with a survey with a questionnaire as a tool and interviews. Path analysis is used to obtain results so that workload is found to have a positive effect on job satisfaction.